Review of Hepatitis B Vaccination in Children of Workers of an Oil & Gas Industry in Lho'seumawe and Lho'sukon, North Aceh - Chairul Adillah Harahap; Sari Leyli Harahap; Chairuddin P. Lubis; Ahmad Judin (Paediatrica Indonesiana, 1994)
We describe a retrospective study on hepatitis-B immunization in the Indonesian workers' children of Mobil-Oil Indonesia Lho' Seumawe and Lho'sukon, North Aceh. Data were obtained from medical records and included all children in the 0-15 years age group who had been immunized against hepatitis B types and schedules of vaccines, pre-immunization seromarkers, and anti HBsAb after the third immunization were recorded. For hundred and twenty children had received three doses of,hepatitis B vaccines; 180 children had them at 0, 1 and 2 months and the rest at 0, 1 and 6 months. Type of vaccine used was hunian plasma derived vaccine with a dosage of 5 Âµg per shot All of them (except the newborns) were tested and had seromarkers negative to hepatitis 8 infection prior to immunization. Testing for immune response (HBsAb) 2-6 months after the third immunization could only be done in 213 children, where 168 (78.9%) showed HBsAb titer> 10 miU/ml, 5 (2,30Al) had HBsAb < 10 miU/ml, and the remaining 40 (18,8%) showed no seroconversion. Of those 40 children who did not seroconversed, 31 were given a fourth dose, and 14 children were retested for their HBsAb titre. Seven children had positive responses and the rest remained negative.